Kajian Penggunaan APD (Alat Pelindung Diri) dengan Penyakit Akibat Kerja PAK (Penyakit Akibat Kerja) pada Siswa - Mohammat Fairosi; Hadi Nur Efendi; Andi Wapa (Pusat Riset dan Inovasi Nasional, 2024)
This study discusses the use of APD with occupational diseases (PAK) in students because in the field there are many students who do not understand about personal protective equipment and many students do not understand occupational diseases, therefore the purpose of this study is to increase student knowledge about the importance of using personal protective equipment (APD) and increase student knowledge of diseases caused by work or occupational diseases (PAK) so that students avoid occupational diseases (PAK) and emphasize the use of personal protective equipment (APD). The data collection method in this study uses a description using quality by collecting library data, reading and recording and processing research materials. The results of this study are the importance of educating students about the use of personal protective equipment in order to avoid occupational diseases such as physical, chemical, and biological hazards and increasing compliance with the use of personal protective equipment by increasing student knowledge through counseling or providing education and motivating them to use personal protective equipment in order to avoid occupational diseases.